Pengaruh Perkembangan Teknologi Terhadap Kurangnya Literasi Budaya Dan Kewarganegaraan Siswa SD - Rizki Ramdani; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Lembaga Pengembangan Kinerja Dosen, 2024)
This article explores the impact of technological advances on elementary school students' cultural and civic knowledge. Even though it provides broad access to information, the negative impacts of technology such as social isolation and lack of direct interaction with cultural diversity make understanding cultural values and citizenship difficult. Reduced social engagement is also a challenge, limiting students' role as active citizens. The proposed solution involves collaboration between teachers, parents, and communities to create an educational environment that balances technology and hands-on experiences grounded in cultural and civic values. This article emphasizes the importance of preparing elementary school students to acquire strong cultural knowledge and a deep sense of citizenship, helping them become active and responsible members of society.